SODA-AQ PULPING OF PAULOWNIA WOOD AFTER HYDROLYSIS TREATMENT - Juan Carlos García; Minerva A.M. Zamudio; Antonio Perez; Manuel Javier Feria; José Lívio Gomide; Jorge Luiz Colodette; Francisco López (BioResources, 2011)
A trihybrid clone of Paulownia fortunei x tormentosa x elongata was used for pulp and paper production using the soda-anthraquinone (AQ) process, comparing the results with those from Paulownia fortunei. An autohydrolysis process had been previously carried out on this raw material. A composite central experimental design and a multiple regression were used for modeling and optimizing the process. A valuable liquid phase could be obtained from the autohydrolysis process of Paulownia, trying to minimize cellulose degradation for pulp and paper production. A compromise to maximize the glucan and minimize the xylan contents in the postautohydrolysis solid phase could be achieved at 187.5ºC and 15 minutes. A suitable cellulosic pulp with kappa number ranging from 12.2 to 69.2 and ISO brightness from 18.2 to 30.6% presented better results than those from other studies. Regarding handsheets physical properties (tensile index 37.3 N•m/g ) and viscosity (848 cm3/g), significant improvements could be obtained when compared with previous results of a similar process using Paulownia fortunei or Paulownia elongata.